A bio-mimetic cellular structure for mitigating the effects of impulsive loadings – A numerical study. (September 2021) - Ghazlan, Abdallah; Ngo, Tuan; Le, Van Tu; Nguyen, Tuan; Linforth, Steven; Remennikov, Alex; Whittaker, Andrew
Re-entrant and honeycomb cellular structures have shown potential for mitigating the effects of extreme loadings such as those imposed by impacts and near-range air blast. However, these cellular geometries can buckle locally and collapse in the immediate vicinity of the loading, which can limit their effectiveness as a protective element. These deficiencies can be addressed by mimicking alternate, naturally occurring, cellular structures, including that of the porcupine quill, which is studied here. The quill possesses several distinct features that effectively counteract buckling and bending, and minimise weight. This study mimics several structural features of the quill to develop a novel cellular design for counteracting air blast loads such as those associated with detonations of high explosives. The performance of the bio-mimetic structure is benchmarked against traditional hexagonal and re-entrant designs, which have been documented in the archival literature. The quill-inspired structure offers more design freedom than the traditional cellular geometries. By iteratively mimicking several of the structural features of the porcupine quill, an optimal balance between local buckling and collapse can be realised, which minimises the reaction on the target below and maximises energy dissipation.